Somos as palavras que trocamos: uma análise multidimensional do discurso corporativo de empresas nativas e em transformação digital como contribuição ao portal multimodal/multilíngue para avanço das ciências abertas nas humanidades - Dombrasas, Carolina C. Andrade (2023)
At the center of current debates, the Digital Revolution has been transforming structural aspects of life in society. The corporate world is also trying to adjust to the new order, in which traditional companies are pushed towards the digital transformation process to remain competitive - especially against companies that were born and raised connected, the so-called digital natives. Horizontal structures, agile models, updated tools and a culture that encourages collaboration guide this journey. But to what extent does the discourse practiced in companies support this paradigm shift? The present thesis works on the premise that language plays an active role in the journey towards digital transformation and aims to map the linguistic patterns of companies with different degrees of digitization in search of similarities and differences. In this sense, it is supported by the interdisciplinarity of Digital Humanities (ADOLPHS, KNIGHT, 2020) and Corpus Linguistics (BERBER SARDINHA, 2004) to study the discourse of 20 companies, from different segments, with shares listed on the North American stock exchange. The data, protocols and other content produced throughout the research will be made available based on the principles of Open Science, contributing to the institutional proposal 'Multimodal/multilingual portal for the development of open science in the Humanities', presented by PEPG in LAEL to the call CNPq 25/2020. In collaboration with a team of researchers, this project also contributed to the development of the website cienciaaberta.org, which builds bridges between the academy, researchers from other fields/institutions and society by making data available free of charge from all lines of research participating in the project